COLOR REMOVAL FROM TEXTILE WASTEWATER WITH ANAEROBIC TREATMENT PROCESSES - Kaykioglu, Gul; Debik, Eyyup (YILDIZ TECHNICAL UNIV, 2006)
In this study, anaerobic treatment of dyes, which are important considerations during the treatment of textile effluents, were determined. Textile effluents have high strength characteristics and have no regulation in the Water Pollution Control Legislation in our country for the color parameter to discharge to receiving bodies. For this reason, textile effluents were generally treated using aerobic treatment and discharged to receiving bodies with high color. However, today, there are some mandatory rules for color removal from industrial wastewater in developed and developing countries. Therefore, studies on color removal were intensively concerned. Anaerobic color removal in reviewed studies was performed using anaerobic or anaerobic/aerobic sequential reactors by anaerobic or facultative microorganisms. It was concluded from previous studies that color removal from textile effluents was successful using anaerobic-aerobic systems in which anaerobic step achieves effective color removal and aerobic step provides additional COD removal. From our reviews, we believe that if anaerobic treatment unit is installed before the activated sludge systems, which were constructed and in operating condition, receiving bodies can be improved to better status.
Keywords: Textile wastewater; anaerobic; color removal; azo dye; indigo dye; Engineering